Puva therapy in chronic actinic dermatitis: A preliminary study. - Masood Qazi; Sameem Farah; Hassan Iffat; Khan Dilshad; Majid Imran; Bhat Taseer; Singh Gurcharan (Wolters Kluwer Medknow Publications, 2005)
Five patients with biopsy documented chronic actinic dermatitis were treated with PUVA therapy during spring and early summer. Out of these, only one patient remains in remission till date while the other patients relapsed after an average duration of two months.